1997
DOI: 10.1530/eje.0.1370254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of persistent thyroglobulinemia in patients with well-differentiated thyroid cancer

Abstract: Whereas in the past a negative diagnostic 131 I whole body scan (WBS) was interpreted as the lack of significant residual or recurrent thyroid cancer, today the patient with negative WBS and measurable serum thyroglobulin (Tg) presents a diagnostic and therapeutic dilemma. Previous studies have shown a high rate of visualization of uptake and a decrease in Tg after one or more therapeutic doses of 131 I. In order to further assess the significance of this finding, retrospective analysis of patients with persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…We have shown previously that the diet described results in low iodine excretion (22). The findings of several studies support the use of blind treatment with high-dose 131 I in cases of negative diagnostic scanning and increased serum Tg, because a post-treatment decline in serum Tg was observed (Table 6) (6,13,15,23,24). Most studies describe the treatment results only in patients with a positive post-treatment WBS, but the number of patients and follow-up data in these studies were limited (Table 6).…”
Section: Discussionmentioning
confidence: 53%
“…We have shown previously that the diet described results in low iodine excretion (22). The findings of several studies support the use of blind treatment with high-dose 131 I in cases of negative diagnostic scanning and increased serum Tg, because a post-treatment decline in serum Tg was observed (Table 6) (6,13,15,23,24). Most studies describe the treatment results only in patients with a positive post-treatment WBS, but the number of patients and follow-up data in these studies were limited (Table 6).…”
Section: Discussionmentioning
confidence: 53%
“…Subsequent reports demonstrated that more than half of such patients, if given an empiric therapeutic dose of 131 I, had visible uptake on a post-therapy WBS, and the median percentage of positive scans was 57% (range 0-94%) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Most lesions were in the cervical lymph nodes, but thyroid bed uptake (which could represent normal thyroid remnant) and distant metastases were also detected.…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1980s to mid-1990s, several authors reported that if given a therapeutic dose of 131 I, 64-94% of patients with positive serum Tg but negative DxWBS (Tg + /WBS -) would have detectable residual thyroid cancer in a post-therapy 131 I scan (2)(3)(4)(5). Numerous subsequent reports confirmed these early results, and the median percentage of positive post-therapy 131 I-WBS was 57% (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). While many advocated the use of an empiric dose of 131 I, others cautioned against its routine use, given the side effects and unproven benefits (10,(17)(18)(19)(20).…”
mentioning
confidence: 94%
“…As detectable serum Tg usually results in further imaging work-up or even therapy (6,7), this lowest concentration range is of far greater clinical significance for Tg assays than for most other tumor markers; therefore our evaluation was planned to focus particularly on the assay imprecision at the lowest concentration range.…”
Section: Introductionmentioning
confidence: 99%